2022
DOI: 10.1155/2022/1749111
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis-Related Gene Model Predicts Prognosis and Immune Microenvironment for Non-Small-Cell Lung Cancer

Abstract: Non-small-cell lung cancer (NSCLC) has a high incidence and mortality worldwide. Moreover, it needs more accurate means for predicting prognosis and treatments. Pyroptosis is a novel form of cell death about inflammation which was highly related to the occurrence and development of tumors. Despite having some studies about pyroptosis-related genes (PRGs) and cancer, the correlation has not been explored enough between PRGs and immune in NSCLC. In this study, we constructed a PRG model by WGCNA to access the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Primary bronchogenic carcinoma is a malignant tumor that originates from the trachea, bronchus, and lung [ 1 , 2 , 3 ]. Lung cancer is a bronchogenic cancer, examples of which include lung squamous cell carcinoma (LUSC), lung adenocarcinoma (LUAD), small-cell carcinoma, and large-cell carcinoma [ 4 , 5 , 6 ]. Lung cancer has a high incidence and mortality worldwide [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primary bronchogenic carcinoma is a malignant tumor that originates from the trachea, bronchus, and lung [ 1 , 2 , 3 ]. Lung cancer is a bronchogenic cancer, examples of which include lung squamous cell carcinoma (LUSC), lung adenocarcinoma (LUAD), small-cell carcinoma, and large-cell carcinoma [ 4 , 5 , 6 ]. Lung cancer has a high incidence and mortality worldwide [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the three identified genes, BNIP3 has been reported to have an association with osteosarcoma, ovarian cancer, breast cancer, and melanoma prognosis [ 28 , 29 , 30 , 31 ], and BNIP3 is pro-apoptotic in most studies [ 32 ], although there are still some studies indicating that BNIP3 can inhibit apoptosis in tumor cells [ 33 , 34 , 35 ]. Burton et al [ 35 ] reported that nuclear BNIP3 acts as a transcriptional repressor by binding to the promoter region of the AIF gene, thereby preventing apoptosis of glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Burton et al [ 35 ] reported that nuclear BNIP3 acts as a transcriptional repressor by binding to the promoter region of the AIF gene, thereby preventing apoptosis of glioma cells. Luo et al [ 33 ] indicated that knockdown of BNIP3 significantly increased the apoptosis rate of lung cancer cells, and low expression levels of BNIP3 could increase the infiltration of immune cells and improve the prognosis of lung cancer patients. Moreover, the role of BNIP3 in various tumors is inconsistent.…”
Section: Discussionmentioning
confidence: 99%